Bone marrow pathology - Bain, Barbara J (Blackwell Science, 2001)
Written by one of the world\'s leading haematologists, and three renowned histopathologists, Bone Marrow Pathology provides a comprehensive guide to the diagnosis of bone marrow disease. Now in its Third Edition, the text has been extensively revised and rewritten to reflect the latest advances in the field. Features:An extremely practical, up-to-the-minute text incorporating the new WHO classification of haematopoietic malignancies A comprehensive text written with great precision and clarity of style Incorporates a new section \'Problems and Pitfalls\' - a unique section that will aid the working pathologist faced with a difficult situation An important text for the haematologist, histopathologist and haematopathologist with equal weight given to peripheral blood, aspirate, trephine biology and specialized techniques Extensively illustrated with many of the photographs being of paraffin-embedded sections Combines all the techniques now applied to bone marrow diagnosis, including immunocytochemistry, flow cytometery, immunohistochemistry and the diagnostic role of cytogenetic and molecular genetic analysis
Keywords: kostní dřeň; Bone Marrow; Dřeň kostní; patologie; hematologie a transfuzní lékařství; Pathology; Patologie